Burma's forgotten conflicts: A risk for the region's security - Jasmin Lorch; Gerhard Will (Stiftung Wissenschaft und Politik (SWP), 2009)
The trial of Aung San Suu Kyi, leader of the Burmese opposition party NLD, that opened on May 18, 2009, has for weeks been the cause of worldwide outrage. In this situation, it is easy to forget the huge potential for violence that is contained in the conflicts that are coming to a head between the central government and the ethnic minorities. Since 1989 the relative stability of the country rests on the ceasefire agreements that were negotiated with many of the armed minority groups. The attempt of the regime to push through a new, centralist constitution, fans the flames of latent conflict rather than leading to a solution. The resumption of armed conflict would be a huge security risk for the whole region. This threat thus demands that the neighboring countries elaborate a common response, the formulation of which could be mediated by the EU
Keywords: 320